RANCANG BANGUN CETAKAN PLASTIK SARINGAN PEMBUANGAN AIR KAMAR MANDI - Prayetna, Aditya; GINTING, MUCHTAR (Universitas Majalengka, 2022)
The main purpose of the design of plastic molding molds is to participate in advancing the world of the machining industry and can help the mold industry to simplify and shorten the time in doing a work of making molds, especially plastic molding molds. The design of this plastic molding mold by designing the shape of the injection machine then calculates the volume in the injection machine, the volume of this bathroom drain filter mold is 26838,475 mm3. Calculations on the design of this bathroom drain filter mold use references from the book by Scharcus, Edward and Herman Jutjz,